2012
DOI: 10.1016/j.jadohealth.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' and Young Adults' Perception of Homosexuality and Related Factors in Three Asian Cities

Abstract: Purpose Adolescents’ and young adults’ perception of homosexuality plays an important role in the marginalization and stigmatization of the homosexual, thereby influencing his or her health. This article aims to study that perception and to examine its predictors in three Asian cities that are culturally dominated by Confucianism. Methods From May 2006 to January 2007, a cross-sectional survey of 17,016 adolescents and young adults, aged 15–24 years old, in both urban and rural sites of three Asian cities (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
2
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 32 publications
4
42
2
9
Order By: Relevance
“…Similarly as with adults, studies including adolescent samples have found associations between homophobic attitudes and being male (Flood & Hamilton, 2005;Greniez & García, 2008;Horn, 2006;Poteat et al, 2013;Van de Ven, 1994), religious fundamentalism (Marsiglio, 1993), low socio-economic backgrounds (Feng, Lou, Gao, Tu, Cheng, Emerson & Zabin, 2012) and low education (Feng et al, A c c e p t e d M a n u s c r i p t HOMOPHOBIC ATTITUDES IN LATIN-AMERICA 6 2012; Marsiglio, 1993). Contrary to what has been found with adults, these studies have shown that older adolescents or young adults seem to be more tolerant of homosexuality than younger adolescents (Feng et al, 2012;Flood & Hamilton, 2005;Greniez & García, 2008;Horn, 2006;Marsiglio, 1993;Van de Ven, 1994).…”
mentioning
confidence: 99%
“…Similarly as with adults, studies including adolescent samples have found associations between homophobic attitudes and being male (Flood & Hamilton, 2005;Greniez & García, 2008;Horn, 2006;Poteat et al, 2013;Van de Ven, 1994), religious fundamentalism (Marsiglio, 1993), low socio-economic backgrounds (Feng, Lou, Gao, Tu, Cheng, Emerson & Zabin, 2012) and low education (Feng et al, A c c e p t e d M a n u s c r i p t HOMOPHOBIC ATTITUDES IN LATIN-AMERICA 6 2012; Marsiglio, 1993). Contrary to what has been found with adults, these studies have shown that older adolescents or young adults seem to be more tolerant of homosexuality than younger adolescents (Feng et al, 2012;Flood & Hamilton, 2005;Greniez & García, 2008;Horn, 2006;Marsiglio, 1993;Van de Ven, 1994).…”
mentioning
confidence: 99%
“…O discurso dominante a associa ao pecado, crime, perversão, doença, anormalidade. Na área da saúde, a temática que se destaca é a questão da Síndrome da Imunodeficiência Adquirida (AIDS) e da vulnerabilidade ao Vírus da Imunodeficiência Humana (HIV) relacionadas à homossexualidade masculina (4) . Essa realidade é demonstrada nos discursos dos adolescentes, os quais refletem o preconceito velado, bastante comum nos tempos atuais.…”
Section: Preconceito Ou Tolerância: a Identidade De Gênero Para Os Adunclassified
“…São muitos os problemas de saúde pública que se relacionam diretamente com o estudo da sexualidade, como a expansão das Doenças Sexualmente Transmissíveis (DST) e do número de gravidezes inoportunas na adolescência. Não são, entretanto, menos graves aqueles que recebem sua influência indireta, embora marcante, como as violências relacionadas às questões de gênero (3,4) . Embora essas relações atuem em todas as fases da vida, é na adolescência que os valores tidos como "normais" são introjetados, incluindo os modos de relação entre os gêneros (5).…”
Section: Introductionunclassified
“…É sabido que a expansão das doenças sexualmente transmissíveis e o crescente número de gravidezes inoportunas na adolescência são problemas sociais que se relacionam diretamente com o estudo da sexualidade. Não são menos graves aqueles que sofrem sua influência indireta, embora marcante, como a violência de gênero e a violência relacionada às orientações sexuais (TAQUETTE, 2010;FENG et al, 2012).…”
unclassified